Compressive Strength Study on Reactive Powder Concrete with 30% Quartz Sand and Variations in Fly Ash Composition as Partial Substitution of Cement - Safitri, Endah; Wibowo, Wibowo; Fadhil, Bayu Dian (Indonesian Journal Publisher, 2024)
The concrete industry is considered environmentally unfriendly and unsustainable due to the significant consumption of natural materials. Currently, the industry predominantly uses Portland cement as its main ingredient, leading to an increase in Portland cement production. However, the use of fly ash can help make the concrete industry more sustainable in the future. Fly ash can be used as a partial replacement for Portland cement in concrete production. This study aims to determine the effect of fly ash variations on the compressive strength of reactive powder concrete. The research method used is experimental. The concrete mix design includes 30% quartz sand and fly ash variations of 0%, 5%, 10%, 15%, 20%, and 25%. The compressive strength test specimens are cylindrical with a diameter of 7.5 cm and a height of 15 cm. The resulting test specimens have a compressive strength of more than 41.4 MPa, thus qualifying as high-strength concrete. The compressive strength test results for fly ash variations of 0%, 5%, 10%, 15%, 20%, and 25% are 62.62 MPa, 66.27 MPa, 75.59 MPa, 68.78 MPa, 66.21 MPa, and 63.70 MPa, respectively.